Economic Insights Unveiled: A Journey through Input-Output Analysis in Non-Linear Mathematics - Sahani, Suresh Kumar; Jha, Aditya; Sahani, Kameshwar; Prasad, Kripa Sindhu (Darul Yasin Al Sys, 2023)
This project work explores the world of input-output analysis, a powerful economic tool that reveals the complicated web of economic interdependencies that exist within a region or nation. By meticulously exploring the foundations, applications, and implications of this analytical method, we set out on a journey to understand the profound impact it has on economic systems. The project begins with a comprehensive introduction to the theory of input-output analysis, shedding light on its historical evolution and underlying assumptions. It meticulously outlines the step-by-step process of constructing input-output tables and interprets the matrix algebra involved, ensuring that even a novice can grasp the fundamentals. Two hypothetical case studies add practicality to the project, vividly demonstrating how input-output analysis can be applied to real-world scenarios, such as the infrastructure sector, the energy sector, and local economic development. Through these case studies, we witness the transformative potential of this analysis, both in terms of economic growth and sustainable practices. Furthermore, the project explores the strengths and limitations of input-output analysis, paving the way for informed discussions and decisions in the realms of economic policy and planning. In the end, the project leaves no stone unturned, presenting a comprehensive view of input-output analysis as a dynamic instrument that empowers us to unravel economic intricacies, fostering a prosperous and sustainable future.